Using an Inquiry-Based Science and Engineering Program to Promote Science Knowledge, Problem-Solving Skills and Approaches to Learning in Preschool Children. Issue 5 (4th July 2021) - Lin, Xunyi; Yang, Weipeng; Wu, Lizhen; Zhu, Lifen; Wu, Duanping; Li, Hui
ABSTRACT: Research Findings: The present study investigated the effects of a 12-week inquiry-based science and engineering (IBSE) program on preschoolers' science and engineering learning experiences. The treatment versus control condition was randomly assigned to four preschool classes, which included 122 preschoolers ( M = 61.10 month, SD  = 3.73). Statistical analysis revealed that the IBSE treatment group (N = 62) had experienced greater gains over time in physical science knowledge, problem-solving skills, and competence motivation as compared to those in the control group (N = 60), with the between-group effect sizes (Cohen's d ) ranging from 0.27 to 1.28. The baseline functioning was found to moderate the program effects. The IBSE group of children who scored higher in science-relevant problem-solving skills at baseline demonstrated more significant improvements in engineering problem-solving skills relative to the control group. Practice or Policy : This study demonstrates that teaching strategies of engineering design process (EDP) and the 5Es instructional model are supportive of young children's learning with enhanced scientific understanding and skills.